Mycale (Oxymycale) acerata Kirkpatrick 1907 - Goodwin, Claire E.; Berman, Jade; Hendry, Katharine R. (Zenodo, 2019)
Mycale ( Oxymycale ) acerata Kirkpatrick, 1907 (Figure 18) Synonomy: Mycale acerata Kirkpatrick, 1907; Mycale acerata var. minor Hentschel, 1914; Mycale acerata var. sphaerulosa Hentschel, 1914; Oxymycale acerata (Kirkpatrick, 1907). Specimens. BELUM. Mc 2015.552 Gøuvernoren Wreck, Enterprise Island (64°32.407’S, 61° 59.884’W), depth 8–19 m; collected by C. Goodwin and E. Priestley, 12/02/2015; BELUM. Mc 2015.604 Grotto Island, Verdansky Base (Site 1) (65°14.615’S, 64° 15.019’W), depth 14–24 m; collected by C. Goodwin and E. Priestley, 16/02/2015; BELUM. Mc 2015.617 and BELUM. Mc 2015.631 Grotto Island, Verdansky Base (Site 2) (65°14.529’S, 64° 15.451’W), depth 6–18 m; collected by C. Goodwin and E. Priestley, 16/02/2015; BELUM. Mc 2015.649 Rocks near San Martin Islands (65°41.297’S, 65° 20.091’W), depth 6–21 m; collected by C. Goodwin and E. Priestley, 17/02/2015; BELUM. Mc 2015.655 The Minnows, Prospect Point (66°01.642’S, 65° 21.323’W), depth 6–18 m; collected by C. Goodwin and E. Priestley, 17/02/2015.; BELUM. Mc 2015.660 Detaille Island (Site 1) (66°52.373’S, 66° 46.967’W), depth 6–24 m; collected by C. Goodwin and E. Priestley, 18/02/2015; BELUM. Mc 2015.690 Rocks NW of Laktionov Island (65°45.536’S, 65° 47.319’W), depth 6–23 m; collected by C. Goodwin and E. Priestley, 22/02/2015; BELUM. Mc 2015.697 and BELUM. Mc 2015.710 Vieugue Island (65°38.758’S, 65° 12.540’W), depth 10–22 m; collected by C. Goodwin and E. Priestley, 23/02/2015; BELUM. Mc 2015.731 Port Charcot, Booth Island (65°03.853’S, 64° 01.868’W), depth 6–16 m; collected by C. Goodwin and E. Priestley, 23/02/2015; BELUM. Mc 2015.780 Under Spiggot Peak, Orne Harbour (64°37.755’S, 62° 33.018’W), depth 5–21 m; collected by C. Goodwin and E. Priestley, 25/02/2015; BELUM. Mc 2015.807 Neptune’s Bellows, Deception Island (62°59.607’S, 60° 33.601’W), depth 7–18 m; collected by C. Goodwin and E. Priestley, 26/02/2015; BELUM. Mc 2015.833 and BELUM. Mc 2015.836 Diomedea Island (62°12.185’S, 58° 56.760’W), depth 10–18 m; collected by C. Goodwin and E. ...